Preparation and improved photoelectrochemical performance of ternary nano-heterostructure of Bi2S3/CdS/ZnO nanorods. (16th October 2019) - Holi, Araa Mebdir; AL-Zahrani, Asla Abdullah
Abstract: Bi2 S3 /CdS co-sensitised ZnO nanorods (ZnO NRs) photoelectrode was successfully synthesised in four steps. ZnO nanoparticles were prepared using the sol-gel/spin-coating procedure; the hydrothermal method was used to prepare ZnO nanorods and CdS respectively; then, Bi2 S3 was synthesised by SILAR method. The present study investigated the enhancement of photo response for CdS/ZnO NRs by applying a homogeneous covering of Bi2 S3 with different cycles of dipping. Field emission-scanning of electron microscopic (FE-SEM), x-ray diffraction (XRD), Raman scattering, Ultraviolet-visible spectroscopy (UV–vis), and Photoelectrochemical performance were utilised to test the morphological, structural, optical, and photoactivity, respectively. The reason for the origin of improved photoelectrochemical performance of the Bi2 S3 /CdS/ZnO ternary films was basically attributed to the level of potential alignment between the CdS/ZnO and Bi2 S3, which is beneficial for electron-hole pairs separation.